The Impact of Early Marriage: a Literature Review - Evita Rohmaniah; Iis Rahmawati; Muhamad Zulfatul A'la (Jurnal Ners, 2025)
Early marriage is not a new phenomenon that occurs in Indonesia or in other countries. The Statistics Center noted that the incidence or prevalence of early marriage is higher in rural areas with a figure of 27.11% compared to urban areas at 17.09%. The purpose of the study was to analyze the impact of early marriage in Indonesia, so as to obtain strategies and recommendations that have the potential to create positive changes in handling problems that lead to negative impacts on adolescents who marry at an early age. This research method uses Literature Review. The literature search process carried out in this literature review uses the database used in the article in the search for articles in the form of Google Scholar, Pubmed, and scient direct with a publication year range of 2018-2023. The search was carried out using several keywords "Early marriage", "impact", AND "Teenege Girl". The findings of 10 journals show that the significant impact of early marriage on reproductive health in women and the risk of dying during childbirth. 10 articles have been identified related to the impact of early marriage on adolescent girls that have an impact on reproductive health, psychology and physical health. The conclusion is that the impact of early marriage on young women results in reproductive health problems in women, physical, psychological, and psychosocial health. In addition, mental readiness at a young age in facing something new as a mother and wife, requires mental readiness and mature thinking to make a decision to marry at a young age. From the many impacts that occur in young women's marriage, the government has issued a new rule for the maximum age of marriage at 19 years. Early marriage can occur in young women due to various factors, namely, education, economic, and cultural/customary factors.